2012
DOI: 10.1177/1420326x12460067
|View full text |Cite
|
Sign up to set email alerts
|

A Thermal Comfort Investigation of a Facility Department of a Hospital in Hot-Humid Climate: Correlation between Objective and Subjective Measurements

Abstract: A field study on assessing thermal comfort has been performed on one of the large-scale hospitals in Malaysia, a country where the climate is classified as hot-humid. The main objective of this study was to examine the comfort criteria by American Society of Heating, Air conditioning & Refrigeration Engineers, US (ASHRAE) standards in hot-humid regions and also to find the correlation between predicted mean vote (PMV) according to Fanger’s theory and thermal sensation vote (TSV) according to occupant votes. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
1
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 20 publications
2
12
1
6
Order By: Relevance
“…Higher comfort temperature than that prescribed by ASHRAE 55 was required for Malaysians in hospitals [349], which was also corroborated by Azizpour et al [350,351] in the study of a hospital in Malaysia. Based on staff evaluations from nine hospitals, Yau and Chew [352] developed an adaptive thermal comfort model for hospital environments with air-conditioning in a tropical climate.…”
Section: Hospitals Healthcare Facilities and Elderly Centerssupporting
confidence: 79%
“…Higher comfort temperature than that prescribed by ASHRAE 55 was required for Malaysians in hospitals [349], which was also corroborated by Azizpour et al [350,351] in the study of a hospital in Malaysia. Based on staff evaluations from nine hospitals, Yau and Chew [352] developed an adaptive thermal comfort model for hospital environments with air-conditioning in a tropical climate.…”
Section: Hospitals Healthcare Facilities and Elderly Centerssupporting
confidence: 79%
“…Azizpour et al. () examined the ASHRAE comfort criteria in a hot and humid region to find correlations between Fanger's PMV and TSV. They found that the neutral temperatures were 26.8 and 25°C, respectively, with TSV and PMV regression models on operative temperature.…”
Section: Occupant Preference For Warmer Temperatures With Elevated Aimentioning
confidence: 99%
“…Mental state is defined as a psychological outcome response to objective and subjective indicators. 15 Emotion is a subjective output of the mental state, and is defined as a mental response resulted from the interconnection between the brain and the physiological actions of the body. 16 When developing attitudes towards the surrounding environment, emotions are initiated and act as a mediator component in the undergoing perception process; thus, they play a substantial role in generating diverse responses.…”
Section: Introductionmentioning
confidence: 99%